Notas sobre o herói contemporâneo e os limites do discurso terapêutico - Galvão, Michelle Prata (2015)
The following research emerged out of the remark that the main characters from major success TV shows for the last decade are – at first sight – quite unlike from what we usually comprehend as television’s “good guys”. They are contemporary beings frequently portrayed as complicated, unhappy and morally wrong. This description strongly separates them from attributes normally connected to the word “hero”: greatness, honour, strength, character, wisdom, dexterity, value, leadership. On behalf of understanding the possibility of the emergence and the popularization of this profile, and also to investigate if truly exists something distinguishing those from ulterior heroes, the hero’s trace was sought into humanity’s history, since its birth as a myth until its present consolidation. For the purpose of limning this profile, the current paper presents the analysis of two contemporary characters, videlicet, Tony Soprano, from The Sopranos, and Walter White, from Breaking Bad. At last, these analyses are articulated within the therapeutic discourse supported by suffering’s narrative. Considering the socio-historical conditions which allowed therapeutics’ discourse appearance and consolidation, as well as elements pointing at its ‘exhaustion’ while (being) a privileged subjectification discourse.